Comparing the Scale of Web Subject Directories Precision in Technical-Engineering Information Retrieval - Mehrdokht Wazirpour Keshmiri; Bahareh Fozooni (Iranian Journal of Information Processing & Management, 2012)
The main purpose of this research was to compare the scale of web subject directories precision in information retrieval of technical-engineering science. Information gathering was documentary and webometric. Keywords of technical-engineering science were chosen at twenty different subjects from IEEE (Institute of Electrical and Electronics Engineers) and engineering magazines that situated in sciencedirect site. These keywords are used at five subject directories Yahoo, Google, Infomine, Intute, Dmoz, that were web directories high-utilization. Usually first results in searching tools are connected to searching keywords. Because, first ten results was evaluated in every search. These assessments to consist of scale of precision, scale of error, scale retrieval items in technical-engineering categories to retrieval items entirely. The used criteria for determining the scale of precision that was according to high-utilization standards in different documents, to consist of presence of the keywords in title, appearance of keywords at the part of web retrieved pages, keywords adjacency, URL of page, page description and subject categories. Information analysis was according to Kruskal-Wallis Test and L.S.D fisher. Results revealed that there was meaningful difference about precision of web subject directories in information retrieval of technical-engineering science, Therefore this theory was confirmed.web subject directories ranked from point of precision as follows. Google, Yahoo, Intute, Dmoz, and Infomine. The scale of observed error at the first results was another criterion that was used for comparing web subject directories. In this research, Yahoo had minimum scale of error and Infomine had most of error. This research also compared the scale of retrieval items in all of categories web subject directories entirely to retrieval items in technical-engineering categories, results revealed that there was meaningful difference between them. And second theory was confirmed. That Intute with 52 percent had most, and Google with 5.3 percent had least scale of ratio technical-engineering retrieval items to retrieval items in all of categories